Development of a short version of the perceived social support scale: based on classical test theory and ant colony optimization - Yunchou Wu; Jingqi Tang; Zhuoran Du; Ke Chen; Fei Wang; Xiaonan Sun; Guoying Zhang; Yibo Wu (BMC Public Health)
Abstract Background Despite the relatively small number of items on the Perceived Social Support Scale (PSSS-12), there has been a trend toward simplification of the scale in order to minimize testing time. In this situation, some researchers based on the responses of military spouses in the U.S., has simplified the PSSS-12 to develop the PSSS-M6. This study aimed to develop a short version of the PSSS-12 suitable for the Chinese general population. Methods A multi-stage stratified cluster sampling method was employed to collect data from 10,914 residents in 120 cities across the country. After randomly dividing the data into two parts, exploratory analysis and confirmatory analysis were conducted separately. During the exploratory analysis of dataset 1, the scale was simplified using both Classical Test Theory (CTT) and the Ant Colony Optimization (ACO), resulting in one short form for each approach. Additionally, three short forms were obtained by introducing other short forms of the Multidimensional Scale of Perceived Social Support (MSPSS) scale derived from multidimensional item response theory in previous studies. The reliability and discriminant validity of the three short forms were tested. Subsequently, the reliability, validity, model fit and measurement invariance for the two short forms of the MSPSS scale were examined using dataset 2. Results The 6-item short form developed based on the ACO (PSSS-A6) exhibited the best psychometric properties among all the short forms. Moreover, the 3-item short form composed of items with the highest factor loadings in each dimension also demonstrated good psychometric properties. Conclusions In future research, if a short form of the MSPSS scale is needed for measurement purposes, the 3-item short form is suitable for clinical settings, large-scale cross-sectional studies, or longitudinal studies, while the PSSS-A6 is more appropriate for more precise measurements. Trial registration This study underwent ethical review (JNUKY-2021-018) by Jinan University.